Sickness and wealth: the corporate assault on global health (Cambridge, Ma., 2004)
"In this powerful and accessible collection of new essays, international scholars and activists examine how official and corporate actors of globalization-including multinationals, the IMF and World Bank, the World Trade Organization, and "first world" governments-have enacted policies that limit medical access and promote disease and death for many in the poor world. The contributors to Sickness and Wealth provide a history of health and "development" strategies; reveal the grim health consequences of these policies throughout the world; and highlight the work of activists and organizations currently working for improved global health. Edited by affiliates of Health Alliance International, which is based at the University of Washington in Seattle, Sickness and Wealth features lucid explanations on this pressing topic, as well as instructive graphics and strong photography. Sickness and Wealth provides a history and context for health and development strategies; shows how profit-driven "development" policies are being exported to countries throughout the world; and reveals the actual health consequences of profit-driven policies, and highlights the work of several social movements currently confronting globalization and working toward improved health. Authors include Vandana Shiva, revealing the effects of industrial agriculture on poor people's health; Patrick Bond, exposing the political roots of South Africa's cholera epidemic; Evelyne Hong, exploring the role of international agencies and corporations in health care; Seiji Yamada, documenting how militarism and war produce disease; and several writers describing how the struggle for people's health is, itself, becoming globalized."